2019
DOI: 10.1177/1098612x19886398
|View full text |Cite
|
Sign up to set email alerts
|

Hypocholesterolemia in cats: a multicenter retrospective study of 106 cats

Abstract: Objectives The aim of this study was to describe the clinicopathologic findings and associated diseases found in a population of hypocholesterolemic cats referred to two tertiary care facilities. Methods An electronic medical record search was performed at two veterinary university referral centers to identify cats with serum cholesterol values below reference interval between January 2004 and 2016. Clinicopathologic data were reviewed for each case and cats were classified into specific disease categories bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 30 publications
1
4
1
Order By: Relevance
“…As far as we know, this is the first report of the prevalence of hypocholesterolaemia in a diverse population of dogs. The period prevalence of feline hypocholesterolaemia in our study differs from the reported prevalence of 0.3-0.4% at other academic institutions (Bowman et al 2019). This is likely explained by different inclusion methods for the study populations.…”
Section: Discussioncontrasting
confidence: 94%
See 4 more Smart Citations
“…As far as we know, this is the first report of the prevalence of hypocholesterolaemia in a diverse population of dogs. The period prevalence of feline hypocholesterolaemia in our study differs from the reported prevalence of 0.3-0.4% at other academic institutions (Bowman et al 2019). This is likely explained by different inclusion methods for the study populations.…”
Section: Discussioncontrasting
confidence: 94%
“…This association with mortality has also been previously shown in canine aflatoxin hepatotoxicosis and in dogs with severe sepsis resulting from parvoviral enteritis (Yilmaz & Senturk 2007, Dereszynski et al 2008. Although a retrospective study in 106 cats did not find a relationship between mortality and severity of hypocholesterolaemia alone, it did find that when hypocholesterolaemia and hypoalbuminaemia were evaluated together, the odds ratio of non-survival increased to 15.6 (Bowman et al 2019). The relationship of hypocholesterolaemia with death in humans is well established and a similar linear trend to our study was also demonstrated in three human hospitals (Windler et al 1994, Bonville et al 2004.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations